Double diabetes as an effect modifier for adverse perinatal outcome in pregnant women with type 1 diabetes mellitus – a retrospective multicenter cohort study - Malinowska-Polubiec, Aneta; Zawiejska, Agnieszka; Romejko-Wolniewicz, Ewa; Poprawski, Grzegorz; Towpik, Iwona; Brązert, Jacek; Handziuk, Zuzanna; Czajkowski, Krzysztof (Frontiers in Endocrinology, 2023)
Introduction Double diabetes (DDiab) is defined as T1DM coexisting with insulin resistance (IR), metabolic syndrome (MetS), and/or obesity. Little evidence is available regarding how frequent DDiab is among T1DM pregnancies and whether it affects the perinatal outcome in this population. Aims of the study To explore the prevalence of DDiab in early pregnancy in the cohort of pregnant women with T1DM and to examine the association between an early-pregnancy DDiab status and fetomaternal complications characteristic for T1DM in pregnancy. Material and methods A retrospective data analysis of the multicenter cohort of N=495 pregnant women in singleton pregnancy complicated with T1DM followed from early pregnancy until delivery in three tertiary referral centers. DDiab status was defined as T1DM plus pre-pregnancy obesity defined as BMI≥30 kg/m2 measured at the first antenatal visit (DDiabOb), or T1DM plus pre-pregnancy IR defined as eGDR (estimated Glucose Disposal Rate) below the 25th centile for the cohort measured at the first antenatal visit (DDiabIR). Proportions of the adverse pregnancy outcomes were compared between DDiabOb and Non-DDiabOb and between DDiabIR and Non-DDiabIR patients. Characteristics of the study group (data presented as mean(SD) or percentage): age: 30.0(5.1) years; age when T1DM diagnosed: 17.5(8.5) years; T1DM duration: 12.0(7,9) years; microvascular complications (White classes R,F,RF): 11.9%, pre-pregnancy counselling: 26.6%, baseline gestational age: 10.5(4.3) weeks, pre-pregnancy BMI: 23.7(4.3) kg/m2; chronic hypertension: 9.1%, gestational hypertension (PIH) 10.7%, preeclampsia (PET): 3.2%; nulliparity 53.8%, smoking in pregnancy: 4.8%, eGWG: 22.4%, DDiabOB: 10.1%; DdiabIR: 25.2%; LGA: 44.0%, and NICU admission: 20.8%. Results (data from the univariate analysis given as OR(95%CI)): both DDiabOB and DDiabIR status increased the risk for eGWG [23.15 (10.82; 55.59); 3.03 (1.80; 5.08), respectively]. DDiabIR status increased the risk for PET [4.79 (1.68;14.6)], preterm delivery [1.84 (1.13; 3.21)], congenital malformation [2.15 (1.07;4.25)], and NICU hospitalization [2.2 (1.20;4.01)]. Both DDiabOB and DDiabIR accurately ruled out PET (NPV 97.3%/98.3%, accuracy: 88.3%/75.6%, respectively), congenital malformation (NPV 85.6%/88.4%, accuracy: 78.9/69.8, respectively), and perinatal mortality (NPV 98.7%/99.2%, accuracy: 88.8%/74.5%, respectively). Conclusions Double diabetes became a frequent complication in T1DM pregnant population. Double diabetes diagnosed in early pregnancy allows for further stratification of the T1DM pregnant population for additional maternal risk.